Bacterial Profile and Antimicrobial Resistance of Infections Among Hospitalized Burn Patients in Asia: A Systematic Review - Zean Zefenkey; Salah Mahdi Al-Bader; Hama Tellawi (Zanco Journal of Pure and Applied Sciences, 2024)
Burn injuries cause a considered number of deaths, mainly due to infections. Many low and middle-income countries in Asia lack data on the causes of burn infections and their antimicrobials susceptibility patterns. This systematic review was conducted to analyze Asian studies on the main agents of infection among hospitalized burn patients and their antimicrobials resistance to guide the empirical treatment which is very important for nosocomial infection control. A literature search was performed in electronic databases to identify related studies between 2013 and 2022. All the finding studies were screened to ensure compliance with including criteria. After the full screening of the articles, 24 studies were included in this work. The majority of pathogens were gram-negative bacteria (63.5%). The pooled prevalence of isolated bacteria of burn infection revealed that A. baumannii (23.8%), P. aeruginosa (20%), S. aureus (19.7%), and K. pneumoniae (11.5%) were the most frequent. According to the pooled results of Antimicrobial Susceptibility Testing (AST) of the included studies, most strains of isolated bacteria were multidrug-resistant (MDR). For gram-negative bacteria, the susceptibility pattern varies greatly according to the genus. The levofloxacin is the only common effective antimicrobial in different percentages. Methicillin-resistant Staphylococcus aureus (MRSA) accounted for 70.4% of the isolated S. aureus. Vancomycin and linezolid have a high susceptibility for all gram-positive cocci. This review suggests that the empirical therapy of hospitalized burn patients in Asia should depend on the combination of antimicrobials that include levofloxacin to prevent increasing MDR emergence in the future. Further studies should be conducted to confirm the clinical effect of these procedures.